2003
DOI: 10.1007/s00125-002-0980-9
|View full text |Cite
|
Sign up to set email alerts
|

The CAG repeat polymorphism in the androgen receptor gene modulates body fat mass and serum concentrations of leptin and insulin in men

Abstract: Aims/hypothesis. The relationship of androgens to the metabolic syndrome has not been resolved. The polymorphic number of CAG repeats within the androgen receptor gene is inversely associated with the transcriptional activity of target genes.This polymorphism might thus influence testosterone effects on body fat content and serum concentrations of leptin and insulin. The direct and indirect role of androgens within the metabolic syndrome should become clearer if this genetically determined effector is taken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
145
6
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(166 citation statements)
references
References 68 publications
(91 reference statements)
13
145
6
2
Order By: Relevance
“…This contrasts to previous studies reporting a correlation with fasting insulin (22) or an association with the risk for suffering from the metabolic syndrome (23). Remarkably, the directions of the association between the CAG length polymorphism and the metabolic parameters were contradictory in these two studies (22,23).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This contrasts to previous studies reporting a correlation with fasting insulin (22) or an association with the risk for suffering from the metabolic syndrome (23). Remarkably, the directions of the association between the CAG length polymorphism and the metabolic parameters were contradictory in these two studies (22,23).…”
Section: Discussioncontrasting
confidence: 96%
“…Limitations of this study are mentioned, which include the relatively small size of the investigated cohort, although within the range of others exploring Table 3 HOMA %S depending on free testosterone (f-testo) and the androgen receptor CAG repeat length for a 60-year-old man with a body mass index of 30 kg/m 2 as predicted from a regression model (see Table 2 the association of the AR CAG repeat length polymorphism on components of the metabolic syndrome (22,23). Furthermore, we reproduced our results obtained in women suffering from hyperandrogenism (24), which support the relevance of the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be a direct effect of increased AR activity in men with shorter alleles, because the AR has been shown to mediate the inhibitory effects of TT and DHT on mesenchymal stem cell differentiation toward adipocytes (30). Our results are in agreement with Zitzmann et al (2003), who found the same relationship with FM in a crosssectional study involving 106 healthy 20-50-year-old men. The median age of their cohort (28 years) was very close to that of our cohort (25.7 years).…”
Section: Relative Thigh Satsupporting
confidence: 91%
“…The androgen receptor is a steroid hormone-activated transcription factor key to regulating androgen activity in both males and females and responsible for secondary sexual characteristics, sex hormone responses and infertility in both sexes. It has been shown to influence body mass and composition [10,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%